Meningkatkan Kemampuan Membaca Lancar Melalui Metode Repeated Reading pada Anak Disleksia - Ritu Afsandra; Arisul Mahdi; Zulmiyetri Zulmiyetri; Gaby Arnez (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze changes in fluent reading ability in dyslexic children through the application of the Repeated Reading method. The study used a quantitative approach with the Single Subject Research (SSR) method with an A–B design. The subject of the study was a third-grade student at SDN 31 Kumpulan Banang who had dyslexia. Data were collected through a fluency reading ability test based on indicators of reading accuracy, reading speed, and prosody, then analyzed using visual graphic analysis that included analysis within conditions and between conditions. The results showed that the subject's fluent reading ability increased after being given the Repeated Reading intervention. In the baseline condition (A), the subject's reading ability was at a stable level, while in the intervention condition (B) there was a gradual increase in ability until it reached a higher achievement compared to the initial condition. Visual analysis showed a change in direction from a flat trend in the baseline phase to an increase in the intervention phase with an overlap percentage of 0%. These findings indicate that the application of the Repeated Reading method is related to an increase in fluent reading ability in the study subject. However, because the study used an SSR design with a single subject, the results need to be understood in the context of individual changes and cannot be generalized widely.